The long-run real effects of monetary policy: Keynesian predictions from a neoclassical model - Marco Espinosa-Vega; Steven Russell (Federal Reserve Bank of Atlanta, 1998)
In this paper we integrate Diamond's (1965) model of neoclassical production and capital with Wallace's (1984) model of monetary policy in order to study the real effects of two types of monetary policy actions: open market operations and changes in reserve requirements. We show that a permanent easing of open market or reserve policy can produce permanent increases in both the inflation rate and the level (but not the growth rate) of output. We also describe conditions under which the effects of these policies on real interest rates and output can be large relative to their effects on the rate of inflation. When we compare the effects of the two types of policies we find that open market operations are the policy tool that minimizes the change in the inflation rate necessary to achieve a given change in the level of output.
Keywords: 330; Keynesian economics; Monetary policy